Air pollution and cause specific mortality in Athens. Issue 4 (December 1990) - Katsouyanni, K; Karakatsani, A; Messari, I; Touloumi, G; Hatzakis, A; Kalandidi, A; Trichopoulos, D
Abstract : STUDY OBJECTIVE--The aim was to investigate the reported association between air pollution and cause specific mortality in the city of Athens. DESIGN--Cause specific mortality was contrasted between 199 d with high values of air pollution and 2*199 comparison days with low pollution, matched in a 1:2 ratio on the basis of various confounding factors. Statistical analysis was done, taking matching into account, using analysis of variance for randomised blocks. SETTING--The study was confined to the city of Athens, using data obtained between 1975 and 1982. PARTICIPANTS--Cause of death was assessed in all 25 138 persons dying in the 3*199 d studied. MEASUREMENTS AND MAIN RESULTS--Causes of death were evaluated blindly by two medically qualified investigators on the basis of information in the death certificates. Mortality was generally higher during the high pollution days but the difference was more pronounced and more significant for respiratory conditions, even though the number of deaths in this category was smaller than the corresponding numbers in the other two categories examined (cardiac and "other" deaths). CONCLUSION--The results show that the short term association between air pollution and overall mortality in Athens is likely to be causal, since it is particularly evident with respect to respiratory conditions, for which a biological air pollution link is more plausible.